Respuesta :

Answer:

So, we have the equation:

[tex]y=x^3-x^2-9x+9[/tex]

Usually, we have to do trial-by-error methods like using the Rational Root Theorem to factor cubic polynomials. However, while this may seem like a complicated cubic equation to factor, it has a simple trick to make it much easier!

We can actually factor this polynomial through Factoring by Grouping. With this method, we can factor a cubic polynomial. We split the equation into two parts, like this:

[tex]y=x^3-x^2-9x+9[/tex]

[tex]y=(x^3-x^2)+(-9x+9)[/tex]

Which can be simplified to:

[tex]y=(x^2)(x-1)+(-9)(x-1)[/tex]

We took out a factor of x^2 for the first term and a negative 9 for the second term. As we can see, we now have two terms that are the same:

(x - 1)

We can factor out the (x - 1) like this:

[tex]y=(x^2)(x-1)+(-9)(x-1)[/tex]

[tex]y=(x-1)(x^2-9)[/tex]

Now, this is not the most simplified form. See the x^2-9 term? We can use the Difference of Squares.

In general:

[tex]a^2-b^2=(a-b)(a+b)[/tex]

We have the expression:

[tex](x^2-9)=(x^2-3^2)[/tex]

[tex](x^2-3^2)=(x-3)(x+3)[/tex]

Therefore:

[tex]y=(x-1)(x^2-9)[/tex]

[tex]y=(x-1)(x-3)(x+3)[/tex]

Our fully factored form for y=x^3-x^2-9x+9 is:

[tex]y=(x-1)(x-3)(x+3)[/tex]

ACCESS MORE